(untitled) (Ágora Journal, 2024)
This article analyzes the mobilization of the theme of the Cisplatine War by the periodical Astréa between 1826 and 1828. The publication, authored by José Joaquim Vieira Souto and Antonio José do Amaral, was released in Rio de Janeiro starting from June 1826 and closely followed the conflict in the Southern Americas, expressing predictions, inquiries, and above all, critiques of its progression. The aim is to examine the arguments used by the newspaper’s editors when referring to the dispute. The employed analytical methodology is Linguistic Contextualism, which assumes the necessity of deeply understanding the production context of a text to successfully access its meanings. It was concluded that the Fluminense periodic press was a vital space for the publicity of the struggle for Cisplatina, with Astréa being one of the most significant participants in this debate.